FAKTOR-FAKTOR RISIKO FRAUD DIAMOND YANG MEMENGARUHI KECURANGAN LAPORAN KEUANGAN - Kiki Amelia Ikhsan (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to examine the influence of external pressure, ineffective supervision, audit opinion, and change of directors on financial statement fraud in banking companies listed on the Indonesia Stock Exchange for the 2018–2022 period. The research sample was selected using the purposive sampling method from the annual reports of 29 banking companies, and the data were analyzed using logistic regression with SPSS version 26. The results showed that ineffective supervision significantly influenced financial statement fraud, while external pressure, audit opinions, and changes in directors had no significant effect. These findings imply the need for banking company managers to enhance supervision effectiveness to minimize the potential for financial statement fraud that could harm external parties.